SURVEY PEDAGANG KAKI LIMA AREA WISATA RELIGI GUS DUR - Agus Raikhani; Linda Ratna sari (LPPM Stikosa - AWS, 2023)
Street vendors are a serious problem for spatial planning because until now there is no certainty and ease of obtaining facilities and space to accommodate their activities. This condition causes street vendors to carry out activities in any space and strategic locations causing congestion, the conversion of public spaces such as sidewalks and roads into trading locations. The survey was conducted to determine the purpose of the survey to obtain accurate data on the number of street vendors with a description of business turnover, type of business, address business and origin of street vendors. The data collection method used is a quantitative approach using an analytical survey method, namely a survey or research that tries to map the number of street vendors, home addresses, total turnover and types of products. The survey results obtained data and the existence of street vendors, a description of business turnover, type of business, business address and origin of street vendors, specifically for Gusdur's grave